Consumption Behavior perception attitude and the marketing mix of consumers towards the service of Chaiya Moo Krata 2 - Sangklom, Nipon; Bilmanoch, Sasiphan; Sanjit, Korakot (Siam Communication Review, 2023)
This research focusing on the study of consumption behavior perception and attitude to the marketing mix of consumers towards the service of Chaiya Moo Krata 2 where having 5 branches : Permsin Branch, Bangkok University Branch, Kanchanaburi Branch, Rangsit University Branch and Khlong Si Lam Luk Ka branch. The sample group of this research was 400 customers who used the service at Chaiya Moo Krata 2 from all 5 branches. By using a questionnaire to collect data and the statistics used in the data analysis were percentage, mean, standard deviation. The finding indicated that : The demographic characteristics of consumers who used the service at Chaiya Moo Krata 2 found that most of them were female, under 18 years old, having marital status/living together and has a bachelor's degree. Most of them are students/students, income between 10,001 - 20,000 baht per month and have 3-5 of family members. Consumption behavior of consumers who used the service at Chaiya Moo Krat 2 found that most of the consumers used the service at this restaurant least 1 time and at the most 30 times within 6 months. Consumers come to use the service the most during the time of 3:00 PM - 7:00 PM on Saturday and Sunday. However, most consumers tend to bring 1-2 people to join the service at the shop. The group of people that consumers take to join the service is mostly friends. The branch that consumers use the most is Permsin branch. Most consumers use the service by eating at the restaurant. The food set that consumers order the most is a medium size set. However, the agenda that consumers use the most is salary opportunity. Most consumers think that they will come back to use the service at the shop again in the future. In addition, most consumers will recommend someone they know to use the service at this restaurant. The perception of consumers who come to use the service at Chaiya Moo Krata 2 which are the perception of the value, perception of quality and perception of worthiness. Overall, it's at a good level. When considering each issue, it was found that consumers perceived the value first. followed by the perception of quality. and the perceived worth, respectively. Attitudes of the marketing mix of consumers who come to use the service at Chaiya Moo Krata 2, which are location and distribution channels. marketing promotion, price, and products and services Overall, it's at a good level. When considering each issue, it was found that consumers had a good attitude in terms of locations and distribution channels first. followed by marketing promotion, price, and products and services respectively.